2021
DOI: 10.3390/foods10112695
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the Protein Ingredients from Insoluble Oat Byproducts Treated with Food-Grade Enzymes, Such as Amylase, Cellulose/Xylanase, and Protease

Abstract: The manufacture of plant-based drinks has the drawback of a huge production of underexploited press cakes. In particular, the oat press cake is mainly used in feed formulation, whereas added-value applications in human nutrition are scarce. Considering that enzymatic treatments may be useful to improve the nutritional quality of these insoluble byproducts, this study aimed to evaluate whether the treatment with some food-grade enzymes, such as amylase, cellulase/xylanase, protease, and their combination, may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
2
2
Order By: Relevance
“…Generally, plant products contain limiting amounts of protein [29]; however, the proximate composition of the oat okara in this study showed a high protein content of 52% (Table 4) which can be favorable for microbial growth. In comparison to other studies on oat okara, this was a high protein content with comparable studies reporting protein content of around 24-32% [10,11]. The fiber content in the present study (16%) was low compared to other studies on oat okara which have been reporting fiber contents around 26-35% [10,11].…”
Section: Proximate Composition and Water Activitycontrasting
confidence: 76%
See 3 more Smart Citations
“…Generally, plant products contain limiting amounts of protein [29]; however, the proximate composition of the oat okara in this study showed a high protein content of 52% (Table 4) which can be favorable for microbial growth. In comparison to other studies on oat okara, this was a high protein content with comparable studies reporting protein content of around 24-32% [10,11]. The fiber content in the present study (16%) was low compared to other studies on oat okara which have been reporting fiber contents around 26-35% [10,11].…”
Section: Proximate Composition and Water Activitycontrasting
confidence: 76%
“…In comparison to other studies on oat okara, this was a high protein content with comparable studies reporting protein content of around 24-32% [10,11]. The fiber content in the present study (16%) was low compared to other studies on oat okara which have been reporting fiber contents around 26-35% [10,11]. The difference in proximate composition can be due to differences in oat cultivars and production methods [30].…”
Section: Proximate Composition and Water Activitycontrasting
confidence: 72%
See 2 more Smart Citations